The relationship between inflammatory cytokines and in‐hospital complications of acute pancreatitis - Yao, Jiaxin; Zhang, Shuangshuang; Zhou, Fei; Zhuang, Mengting; Fei, Sujuan (Immunity, Inflammation and Disease, 2024)
Objective Acute necrotic collection (ANC), acute peripancreatic fluid collection (APFC), pleural effusion, and ascites are common early complications of acute pancreatitis. This study aimed to investigate the relationship between 12 serum cytokines and the early complications and severity of acute pancreatitis (AP). Methods We retrospectively analyzed the clinical data of 307 patients with AP, and divided them into severe group and mild‐to‐moderate group according to the revised Atlanta classification. Propensity score matching was used to control for confounding factors. Binary logistic regression analysis was used to explore the relationship between cytokine levels and early complications of AP. Results Serum levels of interleukin (IL)‐1β, IL‐5, IL‐6, IL‐8, IL‐10, IL‐17, and tumor necrosis factor‐α were significantly higher in the severe acute pancreatitis (SAP) group than in the non‐SAP group (p < .05). After adjusting for confounding factors, the upper quartiles of IL‐6, IL‐8, and IL‐10 were associated with an increased risk of ANC compared with those in the lowest quartile (IL‐6: quartile 3, odds ratio [OR] = 3.99, 95% confidence interval [CI] = 1.95–8.16; IL‐8: quartile 4, OR = 2.47, 95% CI = 1.27–4.84; IL‐10: quartile 2, OR = 2.22, 95% CI = 1.09–4.56). APFC was associated with high serum levels of IL‐6 (quartile 3, OR = 1.32, 95% CI = 1.02–1.72), pleural effusions were associated with high serum levels of IL‐1β, IL‐6, IL‐8, and IL‐10 (IL‐1β: quartile 4, OR = 2.36, 95% CI = 1.21–4.58; IL‐6: quartile 3, OR = 4.67, 95% CI = 2.27–9.61; IL‐8: quartile 3, OR = 2.95, 95% CI = 1.51–5.79; IL‐10: quartile 4, OR = 3.20, 95% CI = 1.61–6.36), and high serum levels of IL‐6 and IL‐10 were associated with an increased risk of ascites (IL‐6: quartile 3, OR = 3.01, 95% CI = 1.42–6.37; IL‐10: quartile 3, OR = 2.57, 95% CI = 1.23–5.37). Conclusion Serum cytokine levels, including IL‐1β, IL‐6, IL‐8, and IL‐10 may be associated with the occurrence of early complications of AP. In daily clinical practice, IL‐6 may be the most worthwhile cytokine to be detected. Acute necrotic collection, acute peripancreatic fluid collection, pleural effusion, and ascites are common early complications of acute pancreatitis (AP). This study aimed to investigate the relationship between 12 cytokines and the early complications and severity of AP.